ANALYSIS OF FISH CATCHING BUSINESS (RASBORA TAWARENSIS) IN THE LAKE FROM WATER SEAWEING VILLAGE TOWEREN DISTRICT LUT TAWAR DISTRICT ACEH CENTRAL ACEH PROVINCE - Fuad Aramiko.AM; Eni Yulinda; Trisla Warningsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted in August 2017 at Laut Tawar Lake, Toweren Village, Lut Tawar Sub-district, Central Aceh District, Aceh Province. This study aims to determine the gross income and net income of Fish Depik fishing business. And To know the feasibility of fishing equipment Jaring Insang. The method used in this study is the survey method with the number of respondents as many as 30 people, 30 census sampling method.The results of this study indicate a favorable fishing effort based on the catching of Depik fish according to the criteria of gross income and net income. Gross revenue (GI) from fishing equipment business is Rp. 39.593.333, - / Year and net income of shrimp nets fishermen is Rp.14.212.532 / Year. Based on financial analysis based on RCR calculation result of Fish catching business is 1.5 which means this business is profitable and feasible to continue although not large. FRR with the calculation of net income per year / total invetasi multiplied by period, hence obtained FRR result 43,5% bigger than interest rate in banks today 7% and get profit to invested. PPC for 2 years 2 months 12 days which means the greater the value of PPC the longer the payback period of business investment or the smaller the value of PPC the faster the payback period of business investment. Keywords : Business Analysis, Fish Depik, Feasibility Study, Toweren Village.